Chloroplast Ultrastructure in Mutant Strains of Chlamydomonas reinhardi Lacking Components of the Photosynthetic Apparatus - Goodenough, Ursula W. (1969)
The fine structure of the chloroplast of wild-type and 9 photosynthetic mutant strains of Chlamydomonas reinhardi is described. The chloroplast phenotypes of the mutant strains are clearly distinct from the wild type in all but 2 cases. Moreover, strains with similar photosynthetic disabilities have structurally similar chloroplasts. These differences are apparently not the result of altered chlorophyll content, nor of photosynthetic inactivity. It is therefore proposed that the structural alterations are in some way related to the mutant strains' inability to synthesize active components of the photosynthetic electron transport chain.